Factors associated with respiratory symptoms among herbicide applicators and assistant applicators in maize field. Issue 4 (21st April 2022) - Sidthilaw, Sutthinee; Sapbamrer, Ratana; Pothirat, Chaicharn; Wunnapuk, Klintean; Khacha-ananda, Supakit
Abstract: A cross-sectional study was conducted with 3, 291 maize farmers enrolled whose main roles were herbicide applicators and assistant applicators. This study aimed to compare the prevalence of respiratory symptoms and the use of personal protective equipment (PPE) between herbicide applicators and assistant applicators, and determine factors associated with respiratory symptoms. Our results suggest that wheeze and dyspnea were associated with the task on the farm (adj. OR = 10.33 for wheeze and 24.13 for dyspnea), amount of herbicide use (adj. OR = 1.95 for wheeze and 1.41 for dyspnea), frequency of herbicide use (adj. OR = 2.87 for wheeze and 4.08 for dyspnea), not always wearing a mask (adj. OR = 1.49 for wheeze and 3.17 for dyspnea), not always wearing gloves (adj. OR = 2.63 for wheeze and 2.44 for dyspnea), and not always wearing goggles (adj.OR = 2.01 for dyspnea) after adjusting for confounding factors.